Cystatin C and Iris: Advances in the Evaluation of Kidney Function in Critically Ill Dog - Paes-Leme, Fabiola de Oliveira; Souza, Eliana M.; Paes, Paulo Ricardo Oliveira; Gomes, Maderleine Geisa; Muniz, Felipe Santos; Campos, Marco Túlio Gomes; Peixoto, Renata Barbosa; Vaz de Melo, Patricia Donado; Arndt, Marcio H. L.; Costa Val, Adriane (Frontiers in Veterinary Science, 2021)
Critically ill hospitalized dogs are subject to certain complications, being acute kidney injury (AKI) a common one. Early diagnosis is crucial, and Cystatin C (CysC) is a reliable and precocious biomarker. The International Society of Renal Interest (IRIS) states that AKI severity can be assessed by mild changes in creatinine serum levels or reduction of urine output that cannot be considered biomarkers of renal failure or insufficiency. Twenty-eight dogs admitted to the Intensive Care Unit, under risk factors for the development of AKI were evaluated. Blood samples were collected for determination of sCr and CysC at admission and after 24, 48, and 72 hours. Urine output was measured by daily monitoring, measured by collection in a closed system. The results showed the incidence of AKI was 67.9% based on the IRIS criteria and 78.6% based on cystatin C, in critically ill patients' dogs. The measurement of serum cystatin C immediately on admission to the ICU was superior in the early identification of patients with AKI when compared to the IRIS (2016) classification and serum creatinine in critically ill dogs